Perdebatan Seputar Theo, Cosmos, dan Anthropos dalam Filsafat Islam - Fahmi, Muhammad (Jurnal Filsafat "WISDOM", 2004)
Discussion of the Theo, Cosmos, and Antrophos are things thatvery interesting and always actuals in the long time and in tile wheres. The discussion of them were not held by Moslem ansich, but also Non Moslem. This paper reflects of that Theo, Cosmos, and Antrophos perspektif Phylosophy of Islamic. In other word, this paper explains some opinions of the Moslems phylosophys to Theo, Cosmos,ana Antrophos. The Moslems persons were taKen their opinions are: AI-Kindi, AI-Farabi, Ibnu Sina, and Ibnu Rusyd.